انسانی جذبات کو قانون کے ذریعے منظم کرنا: اسلامی قانون اور روایتی سیاق و سباق میں تہوار اور سوگ کے مواقع پر والئی سوات کے فرامین (Al-Qamar, 2025)
Walī Swat, a great ruler at the regime of Swat, had a pivotal role in the development of local laws in Swat.  To strengthen the control of the state on the citizen, he had issued various laws related to several aspects of life. Among these rules, of course, the rules related to the occasions of happiness and sadness. These rules were, indeed, binding in nature; meaning thereby violation of which would result severe punishments.  It was claimed, at that time, that such rules are in line with the principles of Sharī‘ah (Islamic law) and, therefore, ideal to be followed. Some study, however, contradicts this by saying that such rules were made as per the prevailing custom of the region. Others explained, with solid evidence, that such laws were based on the principles of conventional law. The present research endeavors, with length, to investigate all such assertions. The predominant approach, in the present research work, however, is to investigate that whether such rules were in compliance with the principles of Islamic law.  Owing to this, all such prevailing rules are critically analyzed in the light of the Holy Qurān and Sunnah of the Holy Prophet (SW). The work of classical Muslim jurists also cited for the same purpose, however, literature of the Hanafī School was followed more comparatively to others; as this was the formal school of thought in the region.  Further, content analysis technique has been followed where the available secondary data has been critically analyzed.
Keywords: Walī Swat; Sharī‘ah; Islamic Law; Sunnah; Customary Law; Conventional Law; Hanafī School